2011
DOI: 10.1167/iovs.10-6134
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Corneal Epithelial Barrier Function by Krüppel-like Transcription Factor 4

Abstract: Klf4 contributes to corneal epithelial barrier function by upregulating the expression of functionally related subsets of cell junctional proteins and basement membrane components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 46 publications
7
45
0
Order By: Relevance
“…we also provide molecular modeling information on the interactions between biologically active laminin fragments and β1-integrin, which will be important to assist in the design of more potent laminin-based peptides to disrupt this axis, thereby perturbing spermatogenesis for male contraception and to understand the underlying biology that coordinates spermiation and BTB restructuring during spermatogenesis. review review there are cross-talks between hemidesmosome and epithelial TJ barrier function, 44 in particular during tumorigenesis, 45 supporting our earlier observations that a disruption of hemidesmosome function can possibly perturb BTB dynamics. 25,46 Collectively, these observations coupled with recent findings, 25,47,48 including studies using animal models treated with environmental toxicants (e.g., MEHP, 49 bisphenol A 50 ) and male contraceptives [e.g., adjudin, 1-(2,4-dichlorobenzyl)-1H-indazole-3-carbohydrazide, formerly called AF-2364 23,51 ], support the presence of an apical ES-BTB-hemidesmosome functional axis to coordinate and regulate the events of spermiation and BTB restructuring at stage VIII of the epithelial cycle.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…we also provide molecular modeling information on the interactions between biologically active laminin fragments and β1-integrin, which will be important to assist in the design of more potent laminin-based peptides to disrupt this axis, thereby perturbing spermatogenesis for male contraception and to understand the underlying biology that coordinates spermiation and BTB restructuring during spermatogenesis. review review there are cross-talks between hemidesmosome and epithelial TJ barrier function, 44 in particular during tumorigenesis, 45 supporting our earlier observations that a disruption of hemidesmosome function can possibly perturb BTB dynamics. 25,46 Collectively, these observations coupled with recent findings, 25,47,48 including studies using animal models treated with environmental toxicants (e.g., MEHP, 49 bisphenol A 50 ) and male contraceptives [e.g., adjudin, 1-(2,4-dichlorobenzyl)-1H-indazole-3-carbohydrazide, formerly called AF-2364 23,51 ], support the presence of an apical ES-BTB-hemidesmosome functional axis to coordinate and regulate the events of spermiation and BTB restructuring at stage VIII of the epithelial cycle.…”
Section: Introductionsupporting
confidence: 67%
“…There are also studies in the literature illustrating that volume 1 issue 3 which is not unexpected since laminin is a known substrate of MMP-2 and MMP9, 66,67 (note: in the rat testis, MMP-9 is restricted to the basal ES at the BTB, 51 and MMP-2 is limited to the apical ES 23 ). Studies have shown that fragments generated from laminin chains following cleavage by MMPs, as well as laminin chains containing biologically active domains, act as biologically active peptides that can regulate cell movement, 67,68 junction or barrier function, 44,69,70 and tumorigenesis. 71,72 We envisioned that laminin-333 at the apical ES might contain biologically active domains, so that upon cleavage by MMP-2 to prepare for the release of sperm at spermiation, these biologically active domains would be released from the apical ES to seminiferous epithelium displays a highly restricted spatial and temporal stage-specific expression.…”
Section: The Apical Es-btb-hemidesmosome Axis In the Seminiferous Epimentioning
confidence: 99%
“…Mechanistically KLF4 is a critical regulator of a genetic network of factors regulating corneal homeostasis, such as aquaporin-3, crystallins, Aldh3A1 and TKT, and epidermal keratinocyte differentiation markers (52). Additionally, it was shown that KLF4 contributes to corneal epithelial barrier function by upregulating the expression of functionally related subsets of cell junctional proteins and basement membrane components (53). KLF4 is also required for lens maturation, but not for retinal cell differentiation (54,55).…”
Section: Physiological Functions In Tissues and Organsmentioning
confidence: 99%
“…Klf4 -null mice die within 15 h after birth due to late-stage defects in skin development (Segre et al, 1999). Conditional disruption of Klf4 in the head surface ectoderm derived tissues results in corneal epithelial fragility, stromal edema, loss of conjunctival goblet cells and a small lens with extensive vacuolation in the anterior corticular region (Swamynathan et al, 2011; Swamynathan et al, 2007). Microarray comparison of the wild type (WT) and Klf4 -conditional null ( Klf4 CN) corneal gene expression suggested that Klf4 contributes to corneal homeostasis by regulating the expression of genes involved in cell cycle progression, cell-cell adhesion, epithelial barrier formation, expression of corneal crystallins, and maintenance of corneal hydration (Swamynathan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%